Model for the diagnosis of quality in service processes: A case study applied to a private higher education institution. Issue 1 (1st January 2019) - Canciglieri Junior, Osiris; Zierhut, Ronaldo Trentin; Mattioda, Rosana Adami; Estorilio, Carla Cristina Amodio; Steiner, Maria Teresinha Arns; Neto, Pedro José Steiner
Abstract: In an increasingly competitive environment, the quality of the services offered by organizations is a decisive factor to ensure their success. Most of the time, the service can be defined as a series of activities of an intangible nature, occurring through the interaction between the company and the client, and leading to the ownership of something not associated to a physical product. Therefore, the service quality is related to the management of their processes, and their improvement becomes difficult due to simultaneity between production and customer participation. The identification of the critical requirements for the customer during each interaction and translating them into performance specifications will provide greater control and the identification of potential failures that may occur during service. This study's objective is to propose a conceptual model for quality diagnosis in service processes. Its methodology was defined in four specific stages: 1. Identify recent publications that address the topic under study; 2. Identify, among these publications, the main approaches suggested by the authors for the quality management of processes in services; 3. Propose a conceptual model for this research, contemplating the identified approaches; 4. Validate the proposed model through a case study at a higher education institution (HEI). Through the application of the four methodology phases, it was possible to identify the critical moments of the HEI service cycle, analyze its failures and identify the improvements to be implemented.